Improving scientific and methodological support for training in paralympic sports - Vorobyev S.A. ,; Baryaev A.A. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to formation of directions for improving the scientific and methodological support of Paralympic sports in the system of sports training. Methods and structure of the study. Currently, scientific and methodological support for Russian sports teams is carried out using modern technologies for collecting and analyzing data on the functional state and level of preparedness of athletes, which make it possible to remotely analyze the measured parameters and provide data to coaches in a fairly short time. Results and conclusions. The article discusses approaches to improving scientific and methodological support for the training of Paralympic sports athletes based on the experience of implementing this system at the St. Petersburg Research Institute of Physical Culture. As the main areas of improvement, the requirements for programs, calendar plan, programs of specific events, means and methods are analyzed, taking into account the differences in sports disciplines and nosological characteristics of Paralympic athletes: sports of persons with musculoskeletal disorders (MSD), sports of the blind, sports of persons with disabilities intellectual disabilities (ID).